1132 The Effect of Platelet Count on Successful Medical Closure of Patent Ductus Arteriosus. (October 2012) - Nath, P; Avondo, M; Roy, R
Abstract : Background and Aim: Patent Ductus Arteriosus (PDA) is a shunt vessel connecting the pulmonary artery and the aorta. It usually closes after birth, but persistence of PDA in preterm neonates is a major cause of morbidity and mortality. A recent study suggested that platelet counts are likely to contribute to PDA closure in humans. We aim to investigate relationship between platelet counts and closure of PDA after medical treatment with Indomethacin or I buprofen. Methods: All preterm infants born ≤ 32 weeks and birth weight ≤ 1500 grams born between 01 January 2008 and 31 December 2010 were included. Retrospective data was collected from the case records, SEND neonatal database and laboratory result systems. Results: A total of 58 babies were identified with 64 episodes of medical treatment for PDA with Indomethacin or Ibuprofen. Mean gestational age was 25.5 weeks and birth weight of 737.1 grams. Mean age at treatment was 26.7 weeks with pre-treatment PDA size of 1.5–6 mm and platelet count of 34–602×10 9 /L. Overall 73% (47/64) were treated with high dose and 11% (7/64) with low dose Indomethacin. 30% (19/64) PDA closed post treatment, 62% (40/64) remained open. Out of 19 successful closures 7 had initial platelet counts of >150 (Odds Ratio 0.31, 95% Confidence Interval) and out of 40 unsuccessful closures 26 had initial platelet counts of >150 (Odds Ratio 3.18, 95% Confidence Interval). Conclusions: Success of PDA closure after medical treatment was not related to the platelet counts in our study group.